2018
DOI: 10.4314/jfas.v9i4s.55
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the effects of P. ostreatus spent mushroom compost and BAP hormone towards C. nutans in vitro culture

Abstract: Realization in minimizing production cost for in vitro culture had brought to a study on application of P. ostreatus spent mushroom compost

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…Both powdered and extracts SMC had emerged positive feedback on the production of shoots with varieties of length. There is similar finding as recoded for Hashim et al (2017). However, the extracellular enzymes in the extracts exerted an effect by elongating the cell wall of the plants and provide a rapid secondary growth (Hayashi et al, 2005).…”
supporting
confidence: 77%
“…Both powdered and extracts SMC had emerged positive feedback on the production of shoots with varieties of length. There is similar finding as recoded for Hashim et al (2017). However, the extracellular enzymes in the extracts exerted an effect by elongating the cell wall of the plants and provide a rapid secondary growth (Hayashi et al, 2005).…”
supporting
confidence: 77%
“…It is widely cultivated in tropical Asia and has long been utilized as a medicinal plant in China, Thailand, and Malaysia [5,6]. The plant has long been used in the folk medicine due to the potential health promoting and pharmacological attributes [7], which are mainly ascribed to the presence of antioxidant constituents such as phenolic acids and flavonoids [8,9,10] According to Intan Suraya et al [11], an ethnobotanical survey in Singaporean communities revealed that C. nutans fresh herbs are consumed as a traditional medicine for its general detoxification purposes. The antioxidant activity is explained due to the presence of phenolic chemicals such as flavonoids, anthocyanins, and others [12].…”
Section: Introductionmentioning
confidence: 99%